Psychoanalysis Feminism of the Representation of Patriarchy and Autonomy of Woman Character in John Steinbeck’s of Mice and Men - Amanda Zifa Aurora; Prayudias Margawati (Universitas Islam Negeri Palopo, 2025)
This article aims to analyze the psychoanalysis feminism of the representation of patriarchy and woman autonomy of the character Curley’s wife in John Steinbeck’s Of Mice and Men. The analysis is conducted using a descriptive qualitative approach, applying Juliet Mitchell’s theory of psychoanalysis feminism to describe the woman’s condition during the American Great Depression through the character of Curley’s wife, who is not named and experiences various forms of oppression as impacts of the patriarchal system. The results show that Curley’s wife is portrayed as a character who goes against patriarchal norms. She exhibits various emotional and behavioral responses due to the psychological and social pressures she experiences. Patriarchy affects Curley’s wife’s self-perception and social interactions, causing her to feel deep loneliness and frustration. Through psychoanalysis and feminist analysis, this study reveals how gender norms and patriarchal structures shape women’s psychological conditions. Curley’s wife experiences alienation, loneliness, and lack of power in the patriarchal structure that exists in the environment where she lives. Mitchell says that the pervasive suffering experienced by women highlights that extreme physical violence is an ever-present threat. This persistent fear becomes a defense mechanism against their loneliness and a means to cope with male domination. Additionally, their behaviors, often perceived as flirtatious, are ways to express a deep-seated desire to escape the constraints of patriarchy. Curley’s wife’s flirtatious nature becomes a defense mechanism against her loneliness, a way to deal with Curley’s domination, and a way to express her desire to escape patriarchy.